2021
DOI: 10.1021/acs.langmuir.1c00921
|View full text |Cite
|
Sign up to set email alerts
|

Precise Evaluation of Spatial Characteristics of Periodically Precipitating Systems via Measurement of RGB (Red, Green, and Blue) Values of Pattern Images

Abstract: In the present study, a method is described for precise determination of spatial characteristics of Liesegang bands formed by employing a classical 1D setup using a web-based free resource (). The method involves the compartmentalization of the information on each pixel into R (red), G (green), or B (blue) values from the pattern images obtained using a simple digital camera. The values can further be converted to absorbance values by using the system blank. Each trough (or peak) in the graph of RGB values (or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Figure a shows the transmission mode photograph of the Cu–8HQ PP bands. Spatiotemporal characterization of the banding patterns was performed using the images obtained at the end of experiments using the RGB method previously reported in our laboratory (Figure b) . In this, the intensity of the blue color was plotted against the distance of the n th band.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a shows the transmission mode photograph of the Cu–8HQ PP bands. Spatiotemporal characterization of the banding patterns was performed using the images obtained at the end of experiments using the RGB method previously reported in our laboratory (Figure b) . In this, the intensity of the blue color was plotted against the distance of the n th band.…”
Section: Resultsmentioning
confidence: 99%
“…Spatiotemporal characterization of the banding patterns was performed using the images obtained at the end of experiments using the RGB method previously reported in our laboratory (Figure 2b). 28 In this, the intensity of the blue color was plotted against the distance of the nth band. The generic parameters of the LP systems, such as the spacing coefficient, p [X n+1 /X n = (1 + p)], where X is the distance of the band from the center of the plate and n is the band number (Figure 2c), the width law, and the diffusion coefficients were determined.…”
Section: Formation Of Lp and Spatial−temporal Analysismentioning
confidence: 99%
“…The phenomenon has several hallmarks such as the distance between two consecutive bands and the width of the precipitation zones increasing with the band number. 12,13 The last 120 years of research on periodic precipitation have been focused on the chemical systems comprising hydrated (usually inorganic) ions. 2 In the past decade, the research of these reaction−diffusion systems shifted toward the pattern design using other types of building blocks such as charged nanoparticles 14,15 and gas-phase compounds in aerogels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This difference in the concentrations of reagents ensures that the pattern formation is driven by the diffusion front of the invading electrolyte. The phenomenon has several hallmarks such as the distance between two consecutive bands and the width of the precipitation zones increasing with the band number. , The last 120 years of research on periodic precipitation have been focused on the chemical systems comprising hydrated (usually inorganic) ions . In the past decade, the research of these reaction–diffusion systems shifted toward the pattern design using other types of building blocks such as charged nanoparticles , and gas-phase compounds in aerogels. , Recently, it has been demonstrated that the components of the zeolitic imidazolate framework-8 (ZIF-8), zinc ions and 2-methylimidazole (2-Met) molecules, in a gelled medium generated spatially continuous and periodic spatial appearance of ZIF-8 crystals with increasing size. , ZIFs are a special class of metal–organic frameworks (MOFs) that are topologically isomorphic with zeolites. These materials have unique physical (e.g., great surface area and thermal stability) and chemical (e.g., significant transition metal containment) properties, and they are widely used in gas storage and separation, chromatography, electronics, organic chemical catalysts, and targeted drug delivery. Therefore, the development of any novel synthesis methods plays a central role in the research of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…This has been explored in many different application, such as for analysis of wine 13 , 14 , ketchup 15 , detection of explosives 16 , 17 , detection of bacteria 18 , etc. 19 21 . A great number of studies on the currently applications of smartphones in analytical chemistry is reviewed elsewhere 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%